Persistent elevation of neutrophil extracellular traps is an independent predictor for non-ambulatory functional outcome in acute ischemic stroke patients with successful recanalization post-endovascular therapy - Yige Zhang; Liyuan Wang; Yuwan Cui; Guangshuo Li; Yahui Hao; Zhixin Cao; Zhixin Li; Ganghua Feng; Hao Wang; Xinmin Fu; Ziqi Xu; Wenhua Liu; et al. (Journal of Cerebral Blood Flow & Metabolism, 2026)
Neutrophil extracellular traps (NETs) contribute to microvascular dysfunction and may predict poor outcomes after successful endovascular treatment (EVT) for acute ischemic stroke (AIS). We investigated dynamic changes in NETs biomarkers (myeloperoxidase-associated DNA complexes (MPO–DNA) and citrullinated histone H3 (CitH3)) and their prognostic value for non-ambulatory functional outcome. In this prospective multicenter cohort, 114 AIS patients with successful recanalization after EVT underwent serial biomarkers measurement at baseline, at 24 h post-EVT and at 7 days/discharge. Primary outcome was non-ambulatory functional outcome (90 days modified Rankin Scale (mRS) 4–6). Generalized estimating equation (GEE) assessed trajectory differences between outcome groups. Logistic regression identified independent predictors. MPO–DNA increased from baseline (341.34 (280.72–442.81)) to 24 h (472.29 (386.35–571.09); p < 0.01) and decline at 7 days/discharge (327.74 (268.17–397.99); p < 0.01 vs at 24 h). CitH3 showed non-significant increase at 24 h (14.022 (9.322–25.783)) vs baseline (12.107 (8.810–21.327); p = 0.16) but significant decrease at 7 days/discharge (11.302 (2.824–21.540); p = 0.01 vs at 24 h post-EVT). GEE revealed a significant time-by-group interaction for CitH3 ( p = 0.01), but not for MPO–DNA ( p = 0.18). Elevated CitH3 7 days/24 h ratio was independently associated with non-ambulatory functional outcome after multivariable adjustment (aOR = 1.99, 95% CI: 1.06–3.72, p = 0.03) with age, baseline National Institutes of Health Stroke Scale (NIHSS), ischemic core volume, and hemoglobin A1c (HbA1c) >6.0% as covariates. Persistent elevation of NETs during 24 h to 7 days is independently associated with post-EVT non-ambulatory functional outcome.